PS-BPC09-3: THE ASSOCIATION BETWEEN THE FRAILTY CLASSIFICATION AND ANTIHYPERTENSIVE TREATMENT IN OLDER PATIENTS: A CROSS-SECTIONAL STUDY. (January 2023) - Akasaka, Hiroshi; Yasunobe, Yukiko; Onishi, Yuri; Minami, Tomohiro; Sugimoto, Ken; Yamamoto, Koichi; Rakugi, Hiromi
Abstract : Objective: The prevalence of frailty and hypertension are both increases with age. However, the treatment target in older hypertensive patients with frailty has not yet been clearly defined. Therefore, we conducted a registry study to clarify the current status of antihypertensive treatment for older patients at our institution. Design and method: We recruited the study participants from consecutive patients who visited the Department of Geriatrics and Hypertension, Osaka University Hospital, between April 2012 and March 2022 and underwent physical function tests and comprehensive functional assessment. We obtained the data on blood pressure and treatment regimen from the medical record. All participants gave informed consent, and our institutional review board approved the study protocol. We defined frailty according to the Japanese version of the cardiovascular health study (J-CHS) criteria. Then, we performed a cross-sectional analysis of frailty and antihypertensive treatment. Results: The participants were 1, 228 (537 men, aged 75.1 + /-8.5 years), classified according to the J-CHS criteria: 234 (19.0%) robust, 778 (63.4%) pre-frail, and 216 (17.6%) frail. The percentage of antihypertensive medication use was lower in the order of frail/ pre-frail/ robust (chi-square 6.71, p = 0.035). Blood pressure levels were not associated with the frailty classification. When examined by gender, neither antihypertensive treatment nor blood pressure was associated with frailty classification in women. On the other hand, in men, the antihypertensive treatment decreased with an increasing degree of frailty, and blood pressure values and pulse pressure tended to increase. Still, the mean office blood pressure in the male frailty group was 127/69 mmHg. The association between frailty classification and antihypertensive medication remained significant after adjustment for age and gender. Conclusions: At our institution, we found that antihypertensive prescriptions have decreased with the degree of frailty in older patients, especially men. The reasons for withholding antihypertensive treatment for frail older patients and its impact on the risk of cardiovascular disease require further investigation.